Многорядные кольца - Кириченко, В.В.; Яременко, Ю.В. (Український математичний журнал, 1996)
Введено многорядні (n-рядні) кільця та розглянуто їх властивості. Вивчено міyори 2-го порядку таких кілець. Наведено вигляд сагайдаків нетерових та спадкових n-рядних кілець. Описано будову иавіппервииних та спадкових n-рядних кілець. We introduce the notion of multiserial (n-serial) rings and study their properties. The second-order minors of such rings are investigated. We also find all possible forms of quivers for Noetherian and hereditaryn-serial rings and describe the structure of semiprime and hereditaryn-serial rings.